Pattern Separation and Source Memory Engage Distinct Hippocampal and Neocortical Regions during Retrieval - Stevenson, Rebecca F.; Reagh, Zachariah M.; Chun, Amanda P.; Murray, Elizabeth A.; Yassa, Michael A. (The Journal of neuroscience, 2020)
Detailed representations of past events rely on the ability to form associations between items and their contextual features (i.e., source memory), as well as the ability to distinctly represent a new event from a similar one stored in memory (i.e., pattern separation). These processes are both known to engage the hippocampus, although whether they share similar mechanisms remains unclear. It is also unknown if, and in which region(s), activity related to these processes overlaps and/or interacts. Here, we used high-resolution fMRI to examine the contributions of hippocampal subfields and neocortical areas to pattern separation and source memory with an experimental paradigm that concurrently tested both. During encoding, male and female human subjects incidentally studied items in one of four quadrants on the screen. During test, they viewed repeated items (targets), similar items (lures), and new items (foils) and were asked to indicate whether each item was old, similar, or new. Following each item judgment, subjects were asked to indicate the quadrant in which the original stimulus was presented. Thus, each lure trial had a lure discrimination component (taxing pattern separation) and a location judgment (source memory). We found two main response profiles: (1) pattern separation-related signals in DG/CA3 and perirhinal cortex and (2) source memory signals in posterior CA1, parahippocampal cortex, and angular gyrus. Whole-brain voxelwise analysis revealed that activity related to lure discrimination and source memory was largely nonoverlapping. These findings suggest that distinct processes underlie the retrieval of pattern separated item representations and recollection of source information. SIGNIFICANCE STATEMENT Recalling past events with detail and accuracy depends on the ability to remember the contextual features of an event (i.e., source memory) as well as the ability to distinguish among similar events in memory (i.e., pattern separation). Previous work has shown that these processes are behaviorally dissociable (e.g., people can have clear memory for context but misidentify people or items). However, both processes engage the hippocampus, and it is unclear whether they rely on shared or distinct neural mechanisms. Here, we used high-resolution fMRI to concurrently assess hippocampal and neocortical activity related to source memory and pattern separation. We found that activity related to these processes was largely nonoverlapping, shedding light on two complementary but distinct mechanisms supporting episodic memory.